2014
DOI: 10.3389/fpls.2014.00676
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping of legume orthologs reveals high conservation of synteny between lentil species and the sequenced genomes of Medicago and chickpea

Abstract: Lentil (Lens culinaris Medik.) is a global food crop with increasing importance for food security in south Asia and other regions. Lens ervoides, a wild relative of cultivated lentil, is an important source of agronomic trait variation. Lens is a member of the galegoid clade of the Papilionoideae family, which includes other important dietary legumes such as chickpea (Cicer arietinum) and pea (Pisum sativum), and the sequenced model legume Medicago truncatula. Understanding the genetic structure of Lens spp. i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 74 publications
3
33
1
1
Order By: Relevance
“…In the present study, comparative analysis was performed between the M. truncatula genome and the gene sequences associated with markers assigned on the consensus map. As previously reported (Sharpe et al, 2013; Gujaria-Verma et al, 2014; Kaur et al, 2014), direct and simple correspondences are observed between M. truncatula pseudomolecules and lentil LGs, although some evolutionary translocations and non-colinear relationships were also detected.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the present study, comparative analysis was performed between the M. truncatula genome and the gene sequences associated with markers assigned on the consensus map. As previously reported (Sharpe et al, 2013; Gujaria-Verma et al, 2014; Kaur et al, 2014), direct and simple correspondences are observed between M. truncatula pseudomolecules and lentil LGs, although some evolutionary translocations and non-colinear relationships were also detected.…”
Section: Discussionsupporting
confidence: 80%
“…A number of genetic linkage maps have recently been developed for lentil, through the use of SSR and SNP marker technologies (Sharpe et al, 2013; Gujaria-Verma et al, 2014; Kaur et al, 2014). The cumulative lengths of maps from this study were marginally higher than those from previous studies (Sharpe et al, 2013; Kaur et al, 2014), possibly due to the effects of a higher number of map-assigned markers, or the genetic constitution of mapping populations (potentially influencing rates of recombination).…”
Section: Discussionmentioning
confidence: 99%
“…Gene discovery in lentil can also benefit from studying other legume crops. Lens is closely related to Medicago L. and Cicer L., and conserved synteny has been demonstrated among these three genera (Gujaria‐Verma et al., 2014). Shared chromosomal organization can facilitate gene searches in lentil; having the exome sequence data available for a diverse set of lines makes it possible to search for useful variants based on knowledge from other species.…”
Section: Discussionmentioning
confidence: 99%
“…The total length of the linkage map was 497.1 cM in the current study. In previous lentil mapping studies, lengths of the linkage maps varied from 751 cM to 4060.6 cM (Eujayl et al, 1998;Rubeena et al, 2003;Duran et al, 2004;Hamwieh et al, 2005;Tanyolac et al, 2010;Gupta et al, 2012;De la Puente et al, 2013;Sharpe et al, 2013;Gujaria-Verma, 2014;Ates et al, 2016). The length of the map reported here was shorter than in these previous studies, but the value was close to the findings (751 cM) published by Hamwieh et al (2005).…”
Section: Lentil Linkage Mapmentioning
confidence: 99%